Reflections on the Context and Logistics of CrossBorder Partnerships - Soares, Anthony (Irish Journal of Arts Management and Cultural Policy, 2019)
This paper is reproduction of thoughts shared by Anthony Soares, Acting Director of the Centre for Cross Border Studies at an event exploring crossborder cultural policy in practice, held in November 2018. It describes the discrepancy between the political context within which cross-border working operates and the practicalities of cross-border cooperation and the partnerships this entails on the island of Ireland. It describes the institutional spaces which have promoted increased and improved cooperation and crossborder working in recent years and queries how cross-border working may be taken forward and who funds it in a changing socio-political context, particularly in light of Brexit. A post-script reflecting on the piece at the time of this publication is provided by Jordana Corrigan.